Native Americans, Christianity, and the Reshaping of the American Religious Landscape - Martin, Joel W., 1956-; Nicholas, Mark A. (Book collections on Project MUSE., 2010)
In this interdisciplinary collection of essays, Joel W. Martin and Mark A. Nicholas gather emerging and leading voices in the study of Native American religion to reconsider the complex and often misunderstood history of Native peoples' engagement with Christianity and with Euro-American missionaries. Surveying mission encounters from contact through the mid-nineteenth century, the volume alters and enriches our understanding of both American Christianity and indigenous religion. The essays here explore a variety of postcontact identities, including indigenous Christians, ""mission.